Rancangan Standar Operasional Prosedur (SOP) Requirement Engineering Menggunakan Soft System Methodology - Suryawan, Brilyan Hendra; Mursanto, Petrus (Ridwan Institute, 2021)
A design of Standard Operational Procedure (SOP) requirement engineering on software development in LIPI has been prepared. LIPI is a Non-Ministerial Government Institution involved in conducting research in the field of science. SOP requirement engineering is made using Soft System Methodology (SSM) and implemented Scrum as a software development framework. Scrum is part of the Agile method which is known to rapidly adapt towards change. This SOP is compiled based on literature studies, SBOKâ„¢ Guide as Best Practice, and previous relevant research as a reference to determine the requirement engineering stage in Scrum. The method being applied in this research is the qualitative method. The method to collect data in this research was made by conducting interviews, FGD, document study, and observation. Thematic analysis method was also applied in data processing.The Design of SOP requirement engineering was aimed to be the Guidance or standard guidelines to create a requirement engineering on the software development in LIPI. Lastly, a high quality software that meets the needs of the users is expected, with this design of SOP requirement engineering.